(untitled) (Experimental biology, 2015)
In this article are given species keys of Polygonum L.genus determinant according to modern taxonomiccal system in the Kazakh language. In the genus Polygonum L. are 48 species: P. thymifolium Jaub. et Spach., P. equisetiforme Sibth. et Smith., P. amphibium L., P. sibiricum Laxm., P. amphibium L., P. viviparum L., P. bistorta L., P. nitens (Fisch. et Mey.) V. Petrov., P. hissaricum M. Pop., P. songoricum Schrenk., P. undulatum Murr., P. coriarium Grig., P. bucharicum Grig. – Г. бухарский, P. paronychioides C.A.Mey. – Г. приноготковый, P. pulvinatum Kom., P. biaristatum Aitch. et Hemsl., P. fibrilliferum Kom., P. serpyllaceus Jaub. et Spach., P. rupestre Kar. et Kir., P. molliforme Boiss., P. floribundum Schlecht., P. corrigioloides Jaub. et Spach., P. paradoxum Czuk., P. polycnemoides Jaub. et Spach., P. acerosum Ledeb., P. rottboelloides Jaub. et Spach., P. acetosum M.B., P. heterophyllum Lindm., P. aviculare L., P. hydropiper L., P. mite Schrenk., P. minus Huds., P. gracilius (Ledeb.) Klok., P. salsugineum M.B., P. patulum M.B., P. subaphyllum Sumn., P. junceum Ledeb., P. argyrocoleum Steud., P. inflexum Kom., P. oxanum Kom., P. arenarium Waldst. et Kit., P. pseudoarenarium Klok., P. persicaria L., P . scabrum Moench., P. lapathifolium L., P. tomentosum Schrank., P. convolvulus L., P. dumetorum L.